Assessment of soil quality indicators for rice-based cropping system in Indo-Gangetic plains of West Bengal - TARAFDER, HRIDAY KAMAL; LUNGMUANA; TAMANG, AMRIT (Journal of Soil and Water Conservation, 2025)
Quantifiable derivation of soil quality is prerequisite for the sustainability of cropping system. The experiment was purposively done in 2018 to identify the most appropriate soil quality indicators and to execute the impact of three most prevalent cropping systems (rice-rice, rice-potato-jute and rice-potatomaize) on soil quality in New Alluvial Zone of West Bengal, India. We have collected 72 soil samples (20 cm depth) after completion of 3rd year cropping cycle and analyzed them for seventeen (17) soil attributes including physical, chemical, and biological parameters. Principal components Analysis (PCA) were performed to formulate minimum dataset (MDS) i.e. the key indicators. SQI was formulated based on the quantitative values of the key indicators for the three rice-based cropping systems. The key indicators found for these Indo-Gangetic soils of West Bengal under rice-based cropping system were: organic carbon (%), available potassium, DTPA Fe, DTPA Mn, DTPA Cu, AS (%), MBC and dehydrogenase activity. In rice-rice cropping system (CS1) the soil quality parameters were low (3.20) and are not desirable for soil health and should be prevented for long term cultivation. However, in rice-potato-jute cropping system (CS2), it was found as SQI 3.34 whereas in CS3, it was 3.22. Therefore, CS2 cropping system can be adopted for long term rather than CS1 and CS3 for the betterment of soil quality in this region.